FINANCIAL LITERACY AND DEMOGRAPHIC FACTORS - Mustapha, Mazlina; Jeyaram, Sangita (Journal of Technology Management and Business, 2015)
The purpose of this study is to examine the relationship between financial literacy and demographic factors of Malaysian university students. Data was collected using primary data. Questionnaires were distributed to 300 final year students of business major programs in one of the institutes of higher learning in Malaysia. Hierarchical multiple regression, independent t-test and ANOVA were employed to analyse the data. The results of the study indicate that those students who enrolled in Bachelor in Accountancy and Bachelor in Business Administrations appear to have higher financial literacy compared to students from other courses. The results also suggest that female students have lower level of financial literacy compared to male students, and Chinese students appear to have significantly higher level of literacy than students from other races. The results from this study contribute to the current literature relating to financial literacy particularly in Malaysian settings.